2017
DOI: 10.1097/iae.0000000000001260
|View full text |Cite
|
Sign up to set email alerts
|

Intrapapillary Proliferation in Optic Disk Pits

Abstract: All examined eyes with ODP showed signs of intrapapillary and prepapillary tissue, which developed over time. SD-EDI-OCT and MHz-OCT are able to detect characteristic ODP-related findings and are a useful means to monitor time-related changes within intrapapillary and prepapillary tissue related to ODP and ODP-M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In all our patients without preoperative PVD, preoperative OCT revealed that the epipapillary membrane was present at the excavation sites of the disc, as shown in a recent study [ 17 ]. The hyaloid membrane was attached to not only the optic disc but also the epipapilary membrane in most of these patients.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In all our patients without preoperative PVD, preoperative OCT revealed that the epipapillary membrane was present at the excavation sites of the disc, as shown in a recent study [ 17 ]. The hyaloid membrane was attached to not only the optic disc but also the epipapilary membrane in most of these patients.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, a tunnel-like hyporeflectivity connecting the schisis and the excavation site of the disc observed with SD-OCT preoperatively became obscured from the early stage after surgery [ 21 ]. Intrapapillary proliferation was observed in all of 16 ODP maculopathy eyes [ 17 ]. The proliferation that sequentially developed was likely to cause the development of cavity within the pit [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Other important OCT findings are intrapapillary cavities, intrapapillary proliferations, septum-like structures, and subretinal precipitates which can be detected as a marker for chronicity of maculopathy. 18 , 19 In our patient, one eye had fluid accumulation under the optic nerve head and an intrapapillary septum structure ( Figure 2C ).…”
Section: Discussionmentioning
confidence: 61%